2006
DOI: 10.2135/cropsci2005.10-0371
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of North American Dent Corn from Public to Proprietary Germplasm

Abstract: Current corn (Zea mays L.) hybrids are produced using proprietary inbred lines as parents. These proprietary lines are protected by U.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
263
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(281 citation statements)
references
References 17 publications
14
263
1
3
Order By: Relevance
“…Maize B73 used in the mapping study has been widely used for genome analyses and breeding for several agronomically important traits (Troyer 1999, Mikel andDudley 2006). Also, in our previous study, B73 exhibited a higher degree of flooding tolerance at the seedling stage among the 223 maize accessions (Mano et al 2002), but this accession has not yet been observed to form surface roots during flooding or root aerenchyma development.…”
Section: Discussionmentioning
confidence: 85%
“…Maize B73 used in the mapping study has been widely used for genome analyses and breeding for several agronomically important traits (Troyer 1999, Mikel andDudley 2006). Also, in our previous study, B73 exhibited a higher degree of flooding tolerance at the seedling stage among the 223 maize accessions (Mano et al 2002), but this accession has not yet been observed to form surface roots during flooding or root aerenchyma development.…”
Section: Discussionmentioning
confidence: 85%
“…Twelve genetically diverse lines that represent important heterotic subgroups in the current US maize commercial germplasm base were used in this study ( Johnson, 2008;Mikel and Dudley, 2006), among these, were two public inbreds and 10 proprietary inbreds for which Plant Variety Protection (PVP) has expired (Mikel, 2006) (Supplemental Table S1). These lines served as ancestors in the development of current elite inbreds and represent a vast amount of the genetic diversity in the current US maize commercial germplasm pool.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Mikel and Dudley (2006) compiled a database of maize lines for which Plant Variety Protection (PVP) had expired by 2004, assessing the number of times each line was used as an ancestor in developing new elite inbreds. From this work, 12 inbreds were identified as representing a vast amount of the genetic diversity in the current maize commercial germplasm pool ( Johnson, 2008).…”
Section: Germplasmmentioning
confidence: 99%